Strategic Implementation of P5-PPRA in Developing The Rahmatan lil ‘Alamin Character at MTs Muhammadiyah Mandalle - Akbar, Muh.; Faridi, Faridi; Sunarto, Sunarto (UMSU, 2025)
This study aims to describe the strategy for implementing the Strengthening Project of Pancasila Student Profiles and Rahmatan lil-‘Alamin Student Profiles (P5-PPRA) in developing Rahmatan lil-‘Alamin character among students at MTs Muhammadiyah Mandalle, Gowa Regency. This research employed a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The findings reveal that the implementation of P5-PPRA followed a systematic approach through the stages of planning, implementation, and evaluation. The strategy involved integrating the program into the school’s operational curriculum, establishing a facilitator team, and conducting thematic projects such as “Sampah Berkarya” (“Creative Waste”), designed to raise students’ environmental awareness and enhance collaborative skills. The program's implementation showed positive implications in shaping students’ character, particularly in fostering environmental concern, responsibility, collaboration, and social empathy. These outcomes align with Thomas Lickona’s theory of character education, which highlights three essential dimensions: moral knowing, moral feeling, and moral action. These dimensions are reflected in the integration of character values into learning processes, reinforcement of social activities that cultivate empathy, and students’ active participation in project-based activities. The findings suggest that P5-PPRA serves as a strategic and effective approach for character formation within the framework of moderate and contextual Islamic education.